Parameters of Starch Granule Genesis in Chloroplasts of Arabidopsis thaliana - Malinova, Irina; Qasim, Hadeel M.; Brust, Henrike; Fettke, Joerg (Frontiers in Plant Science, 2018)
Starch is the primary storage carbohydrate in most photosynthetic organisms and allows the accumulation of carbon and energy in form of an insoluble and semi-crystalline particle. In the last decades large progress, especially in the model plant Arabidopsis thaliana, was made in understanding the structure and metabolism of starch and its conjunction. The process underlying the initiation of starch granules remains obscure, although this is a fundamental process and seems to be strongly regulated, as in Arabidopsis leaves the starch granule number per chloroplast is fixed with 5-7. Several single, double, and triple mutants were reported in the last years that showed massively alterations in the starch granule number per chloroplast and allowed further insights in this important process. This mini review provides an overview of the current knowledge of processes involved in the initiation and formation of starch granules. We discuss the central role of starch synthase 4 and further proteins for starch genesis and affecting metabolic factors.